A review of pore-forming agents on the structures, porosities, and mechanical properties of porous ceramics - Azlan, Umar Al-Amani; Abd Rashid, Mohd Warikh; Jalaluddin, Mohamed Lokman; Tamin, Nor Fauzi; Masri, Mohamad Najmi (AIMS Press, 2024)
This review article provided a thorough examination of porous ceramic materials, concentrating on production, characteristics, and the involvement of pore-forming agents. The primary objective of this research was to evaluate the effects of various ceramic materials and pore-forming agents on the structure, porosity, and mechanical characteristics of porous ceramics. The study’s scope included a thorough investigation of key sources of literature, such as academic publications, review articles, and industry reports, to provide a comprehensive understanding of porous ceramic technology. According to the literature review, the selection of ceramic material and pore-forming agents has a significant influence on the pore size distribution, porosity, and mechanical strength of porous ceramics. Various manufacturing methods, including foaming, sintering, and sol-gel procedures, were explored in terms of their influence on porous ceramic microstructure and characteristics. Furthermore, the study emphasized the need to optimize processing settings and select pore-forming agents to obtain the necessary qualities in porous ceramic materials. Overall, this review is useful for researchers, engineers, and practitioners who desire to learn more about porous ceramic manufacturing, characteristics, and applications.